Industrial apprenticeships - another dying Labour tradition? - Oliver, Bobbie (Australian Society for the Study of Labour History, 2007)
Despite extensive changes occurring in the latter half of the twentieth century, the persistence of apprenticeship in Australia stands in stark contrast to its virtual disappearance in some other industrial capitalist countries, such as the United States of America. It has been argued that the apprenticeship system in Australia arose out of late nineteenth century craft union demands that an indentured apprenticeship be a compulsory requirement for the attainment of skilled worker status and pay. Consequently, the apprenticeship system is a strong labour tradition, which, along with compulsory arbitration and trade union membership, undergirded the skilled labour system throughout the twentieth century.In the second half of the twentieth century, the traditional system of five-year apprenticeships for boys entering a skilled trade underwent vast changes, including shortening the overall period of indentures, increasing the proportion of theoretical training, opening the trades to female applicants and, ultimately, introducing a range of short-term traineeships. This paper presents an overview of these changes, and examines their impact in relation to two Western Australian workplaces: the Midland Government Railway Workshops and the East Perth Power Station. The paper poses the question whether the trade apprenticeship has become another threatened labour tradition, and if so, what are the ramifications? Is a system of apprenticeship that benefits the worker, the employee and society by creating a skilled workforce, now regarded as a luxury for which neither government nor private enterprise is prepared to foot the bill? Is it, indeed, yet another labour tradition that has succumbed to the hostile attacks of non-sympathetic governments?